2006
DOI: 10.1107/s1600536806006350
|View full text |Cite
|
Sign up to set email alerts
|

μ-1,1′-Methylenedi-1H-imidazole-κ2N3:N3′-bis[aqua(pyridine-2,6-dicarboxylato)copper(II)] tetrahydrate

Abstract: The title compound, [Cu2(C7H3NO4)2(C7H8N4)(H2O)2]·4H2O, has a dinuclear structure in which each CuII atom is five‐coordinate in a distorted square‐based pyramidal geometry and the 1,1′‐methyl­enedi‐1H‐imidazole ligand adopts a bis‐monodentate bridging mode, linking the CuII atoms. A twofold rotation axis passes through the C atom linking the imidazole rings. The mol­ecules are connected by O—H⋯O hydrogen bonds [O⋯O = 2.748 (3)–2.973 (3) Å].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The conformation of the bim ligands, described by the two torsional angles about the CH 2 -N bonds, is here rigorously C s . In the few known compounds reported in the literature, in which the bim ligand has been structurally characterized [alone: Li (2006); or in metal complexes: Cui et al (2005, 2006), Jin et al (2006), Dong et al (2006), and Hwang et al (2006)], the alternative C 2 conformation was also found. Interestingly, in the [ M (bim) 3 ](ClO 4 ) 2 species ( M =Cu, Zn), both conformers exist (Cui et al , 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The conformation of the bim ligands, described by the two torsional angles about the CH 2 -N bonds, is here rigorously C s . In the few known compounds reported in the literature, in which the bim ligand has been structurally characterized [alone: Li (2006); or in metal complexes: Cui et al (2005, 2006), Jin et al (2006), Dong et al (2006), and Hwang et al (2006)], the alternative C 2 conformation was also found. Interestingly, in the [ M (bim) 3 ](ClO 4 ) 2 species ( M =Cu, Zn), both conformers exist (Cui et al , 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Aiming at extending our studies to slightly more complex species, we have recently started a project on the coordination properties of the novel bis-(1-imidazolyl)-methane (bim) ligand, for which only a few complexes are known (Cui et al , 2005, 2006; Jin et al , 2006; Dong et al , 2006; Hwang et al , 2006). Initially, our studies focused on Group 12 and 16 metals, for which a systematic study of the coordination features of the bim ligand was conducted (Masciocchi et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cui and co-workers reported eight new complexes with 1D, 2D, or 3D framework structures by self-assembly of two structurally related flexible bis(imidazole) ligands with Ag I , Cu II , Zn II , and Cd II salts . The same authors also reported the crystal structure of two other complex Cu II polymers. , Two lithium-based organic−inorganic hybrid materials based on bis(imidazolyl) moieties with interesting topochemical properties have been very recently described. In both cases, lithium exhibits unusually high binding affinity toward the nitrogen atoms of bisimidazole moiety.…”
Section: Introductionmentioning
confidence: 97%
“…For background to and the biological activity of pyridine-2,6dicarboxylic acid, see: Hay et al (2003). For related complexes, see: Dong et al (2006); Guerriero et al (1987); Kjell et al (1993); Abboud et al (1998).…”
Section: Related Literaturementioning
confidence: 99%
“…Pyridine-2,6-dicarboxylate has proved to be a versatile ligand with N,O-chelation and adopts diverse coordination modes (Guerriero et al, 1987;Kjell et al, 1993;Abboud et al, 1998;Dong et al,2006). Recent efforts of our laboratory to synthesize coordination polymers with pyridine-2,6-dicarboxylic acid and 2-propylimidazole with transition metals resulted in the synthesis of the title complex (I).…”
Section: S1 Commentmentioning
confidence: 99%